Soil weed seed bank: Importance and management for sustainable crop production- A Review - Hossain, MM; Begum, M (Journal of the Bangladesh Agricultural University, 2016)
The seed bank is the resting place of weed seeds and is an important component of the life cycle of weeds. Seed banks are the sole source of future weed populations of the weed species both annuals and perennials that reproduce only by seeds. For this reason, understanding fate of seeds in the seed bank can be an important component of overall weed control. When weed seeds enter the seed bank, several factors influence the duration for which seeds persist. Seeds can sense the surrounding environment in the seed bank and use these stimuli to become dormant or initiate germination. Soil and crop management practices can directly influence the environment of seeds in the soil weed seed bank and can thus be used to manage seed longevity and germination behavior of weed seeds. J. Bangladesh Agril. Univ. 13(2): 221-228, December 2015